HUBUNGAN ANTARA STATUS FUNGSIONAL PASIEN STROKE DENGAN BEBAN CAREGIVER KELUARGA - Purba, Wulan Sari; Julianto, Julianto; Purba, Evi Ramayanti (Universitas Prima Indonesia, 2023)
Caregivers are people who have an important role in helping the process of caring for stroke patients, spouses, children, family members, or friends. The study aimed to examine the relationships between the functional status of stroke patients and the burden on family caregivers. The research design was a descriptive correlation. The participants were be composed of 77 stroke survivors', and their families selected by simple random sampling from the Polyclinic Army Hospital TK IV 01.07.01 Pematangsiantar. Data was collected using a questionnaire consisting of demographic characteristics, Zarit Burden Interview (ZBI), and Barthel Index (BI). The Pearson Product Moment test used to identify the relationships between the functional status of stroke survivors and the burden on family caregivers. The main result found that the functional's status of stroke survivors was mild dependence (51.9%), and 76.6% of the burdens of family caregivers were mild to moderate. Functional's status was statistically negatively associated with family caregiver burden (r=-0.505, p<0.001). In conclusion, the burden of family caregivers increases the functional's status score of stroke patients. The study suggested that nurses should maintain to the functional's status as eating, dressing, bathing, dressing, toileting, bowel/bladder continence, walking, climbing stairs, and changing chair/bed, to reduce the family caregiver burden of stroke survivors.